Abnormal brain iron accumulation in obstructive sleep apnea: A quantitative MRI study in the HypnoLaus cohort. (13th July 2022) - Marchi, Nicola Andrea; Pizzarotti, Beatrice; Solelhac, Geoffroy; Berger, Mathieu; Haba‐Rubio, José; Preisig, Martin; Vollenweider, Peter; Marques‐Vidal, Pedro; Lutti, Antoine; Kherif, Ferath; Heinzer, Raphael; Draganski, Bogdan
Summary: Obstructive sleep apnea syndrome (OSA) may be a risk factor for Alzheimer's disease. One of the hallmarks of Alzheimer's disease is disturbed iron homeostasis leading to abnormal iron deposition in brain tissue. To date, there is no empirical evidence to support the hypothesis of altered brain iron homeostasis in patients with obstructive sleep apnea as well. Data were analysed from 773 participants in the HypnoLaus study (mean age 55.9 ± 10.3 years) who underwent polysomnography and brain MRI. Cross‐sectional associations were tested between OSA parameters and the MRI effective transverse relaxation rate (R2*) – indicative of iron content – in 68 grey matter regions, after adjustment for confounders. The group with severe OSA (apnea‐hypopnea index ≥30/h) had higher iron levels in the left superior frontal gyrus ( F 3, 760  = 4.79, p  = 0.003), left orbital gyri ( F 3, 760  = 5.13, p  = 0.002), right and left middle temporal gyrus ( F 3, 760  = 4.41, p  = 0.004 and F 3, 760  = 13.08, p  < 0.001, respectively), left angular gyrus ( F 3, 760  = 6.29, p  = 0.001), left supramarginal gyrus ( F 3, 760  = 4.98, p  = 0.003), and right cuneus ( F 3, 760  = 7.09, p  < 0.001). The parameters of nocturnal hypoxaemia were all consistently associated with higher iron levels. Measures of sleep fragmentation had less consistent associations with iron content. This study provides the first evidence of increased brain iron levels in obstructive sleep apnea. The observed iron changes could reflect underlying neuropathological processes that appear to be driven primarily by hypoxaemic mechanisms.